New Record of Aphid Parasitoids (Hymenoptera: Braconidae) from some areas of the Syrian coast - أبو كف, نبيل; الرستم , آمنة (Latakia University Journal -Biological Sciences Series, 2020)
The parasitic species associated with aphids were studied on bean and cabbage crops in some areas of the Syrian coast during the period from December 2017 and July 2018. The following species have been found on bean: Aphidius ervi Haliday, 1834, Aphidius picipes Nees, 1811, Praon bicolor Mackauer, 1959, Praon volcure Haliday, 1833, on cabbage: Lysiphlebus arvicola Starý, 1961, Lysiphlebus salicaphis Fitch, 1855, Lysiphlebus thelaxis Starý, 1961, Trioxys angelice Haliday, 1833, Trioxys heraclei Haliday, 1833. These nine species of aphid parasitoids from Braconidae family are recorded for the first time in the Syrian coast.